Extensive characterization of the composition and functional activities of five preparations of human platelet lysates for dedicated clinical uses. (17th February 2021) - Delila, Liling; Wu, Yu-Wen; Nebie, Ouada; Widyaningrum, Rifa; Chou, Ming-Li; Devos, David; Burnouf, Thierry
Abstract: Human platelet lysates (HPLs), rich in various growth factors and cell growth-promoting molecules, encompass a new range of blood products that are being used for regenerative medicine, cell therapies, and tissue engineering. Well-characterized dedicated preparations, tailor-made to best fit specific therapeutic applications, are needed for optimal clinical efficacy and safety. Here, five types of HPL were prepared from the same platelet concentrates and extensively characterized to determine and compare their proteins, growth factors, cytokines, biochemical profiles, thrombin-generating capacities, thrombin-associated proteolytic activities, phospholipid-associated procoagulant potential, contents of extracellular vesicles expressing phosphatidylserine and tissue factor, and antioxidative properties. Our results revealed that all five HPL preparations contained detectable supraphysiological levels, in the ca. 0.1 350-ng/ml range, of all growth factors assessed, except insulin-like growth factor-1 detected only in HPL containing plasma. There were significant differences observed among these HPLs in total protein content, fibrinogen, complement components C3 and C4, albumin, and immunoglobulin G, and, most importantly, in their functional coagulant and procoagulant activities and antioxidative capacities. Our data revealed that the biochemical and functional properties of HPL preparations greatly vary depending upon their mode of production, with potential impacts on the safety and efficacy for certain clinical indications. Modes of preparation of HPLs should be carefully designed, and the product properties carefully evaluated based on the intended therapeutic use to ensure optimal clinical outcomes.